Microwave Characterization of Conductive PLA and Its Application to a 12 to 18 GHz 3-D Printed Rotary Vane Attenuator - Márquez-Segura, Enrique; Sang-Hee, Shin; Dawood, Attique; Ridler, Nick; Lucyszyn, Stepan (IEEE, 2021)
This paper demonstrates an ultra-light weight microwave rotary vane attenuator (RVA) manu- factured using polymer-based 3-D printing. In addition, for the first time, conductive polylactic acid (PLA) is rigorously characterized across both X- and Ku-bands (8 to 18 GHz); while acrylonitrile butadiene-styrene (ABS) has similarly been characterized across Ku-band (12 to 18 GHz). Using the results from the conductive PLA characterization process, an electromagnetic model was created for predicting the performance of the RVA. It is shown that, even with its complex internal geometrical features, a mix of both dielectric and conductive PLA building materials, an assembly of multiple parts and a mechanically rotating central section, our experimental proof-of-concept prototype RVA exhibits excellent measured performance across Ku-band. This tunable microwave control device represents a higher-level of functionality for additive manufacturing, when compared to a fixed (i.e., non-movable) 3-D printed structure, opening the way for other groups to routinely 3-D print custom microwave components and subsystems in the not too distant future.
Keywords: Microondas; Impresoras; Rotary vane attenuator (RVA); Additive manufacturing; 3-D printing; Fused deposition modelling (FDM); Polymer-jetting (PolyJet); acrylonitrile butadiene-styrene (ABS); Polylactic acid (PLA); Conductive PLA; Microwave; Dielectric characterization; Circular waveguide; Rectangular waveguide